Reforming Traditional Islamic Education Through Technology-Based Human Resource Empowerment And Adaptive Curriculum - Fajar Harguna Endra Putra; Deden Edi; Hardjadinata; Marhamah; Raihan; Ishak Syairozi (Jurnal At-Tarbiyat: Jurnal Pendidikan Islam, 2025)
Traditional Islamic education has an important contribution in shaping the religious and moral character of Muslims. However, the challenges of the globalization era demand an increase in the productivity of this education in order to produce graduates who are not only superior in spiritual aspects, but also intellectually and professionally competent. This study aims to examine efforts to design human resource empowerment in order to improve the quality of graduates of traditional Islamic educational institutions. The study uses a qualitative approach with a case study method, where data is obtained through observation, interviews and other data sources. The focus of the study includes improving the competence of educators, developing an integrative curriculum between Islamic science and modern science, and 21st century skills training strategies for students. The results of the study indicate that systematic and sustainable human resource empowerment is the main key in encouraging the productivity of traditional Islamic education in order to be able to compete in the modern era without losing its identity. This study recommends synergy between educational institutions, government, and society in building an adaptive, quality, and future-oriented Islamic education system, through the integration of technology in learning at Salafiyah Islamic boarding schools.